Contemporary trends for the treatment of the prisoner in the light of the minimum rules for the treatment of prisoners (Journal of the College of Education for Women, 2019)
The issue of the prisoners' rights and the way of dealing with them is not just a minor orprimary issue according to the contemporary attitudes to deal with criminals, but it is a fatalissue that goes with the development of life and comprehension of human rights. As thecriminal is considered as a human-being who can be reformed and qualified, according to theaims of the contemporary social service the prisoner is regarded as an idle human source whocan be reformed, treated and qualified so as to make him participate to improve his family andsociety in the end.This study aims at reconstructing the prisons bases when applying the laws of the lowestlevel of treatment through the research of oppositions, attitudes in some prisons laws in Iraqand among the lowest level rules in treating prisoners and these rules which wereaccomplished in the first conference of the United States of preservation from crime andCriminals treatment in Geneva convention in 1955.The most important results this study reached are as follows;-Policy of the Iraqi criminal laws still depends on the policy (The Negative Punishment tofreedom )as a basic punishment which overcomes its decisions that dominate its decisions.And it was reflected on the prisons positions that we find most of the Iraqi prisons suffer frombeing over crowded with prisoners. That caused to the unability to classify them ,besides theweakness of education and health service. Consequently ,the reforming states will be far awayfrom its role which is reforming ,qualifying and treating criminals each one according to hiscase to requalifying them to the society.-Most of the reforming organizations ,especially the managers and the staff (for the reformview)that shows ''Applying the negative punishment to freedom in such circumstances thatthe reforming and educational attitude become weak and becom costly for both the societyand the state equally.